Association Between Nurses' Personal Pain Sensitivity Towards Knowledge and Attitude of Pain Management - Siagian, Ernawaty; Simbolon, Idauli (NurseLine Journal; Vol 8 No 2 (2023): November 2023DO - 10.19184/nlj.v8i2.41159, 2023)
Effective pain management requires the right attitudes, judgments, skills, and knowledge that have an impact on pain treatment outcomes. A careful assessment of each individual’s pain sensitivity is invaluable for the prevention, evaluation, and treatment of pain. This study aimed to determine the relationship of pain sensitivity of professional nurses to pain management knowledge and attitudes. The method used in this research is cross-sectional study with a survey design that provides a quantitative picture of pain sensitivity, knowledge, and attitudes towards pain management in a population, by studying a sample of 160 nurses. Pain Sensitivity Questionnaire (PSQ) and Attitudes of Nurses Regarding Pain. The frequency and percentage of knowledge and attitude regarding pain in category lack (96.87%). Pain sensitivity question score are PSQ Minor score in average value 4.63 and PSQ Moderate score in average score 6.15. There is a significant relationship between attitudes and education with a sig 0.017 (P<0.050. There is a significant relationship between knowledge and attitudes with a sig value of 0.022 (P<0.05), there is no significant relationship between knowledge and pain sensitivity with a sig value 0f 0.689 (p<0.05), there is no significant relationship between attitudes and pain sensitivity with a sig 0.0640 (p<0.05). Efforts to improve knowledge, attitudes, skills and pain sensitivity among healthcare professionals are needed, monitored and evaluated by the hospital administration to improve nurses’ skill in paint management for better patient outcomes